Characterization of compounds and essential oils from Curcuma zedoaria, and evaluation of their cytotoxic and apoptotic properties / Devi Rosmy Syamsir - Devi Rosmy , Syamsir (2018)
The phytochemical and cytotoxic studies were carried out on the rhizome of Curcuma zedoaria (Christm) Rosc. known as white turmeric or zedoary locally known as temu putih. C. zedoaria is an aromatic perennial herb, belonging to the family Zingiberaceae. It has been used in traditional and alternative medicine to treat various ailments including cancer in Asian countries. The phytochemical studies of the Indonesian C. zedoaria crude extracts were done by bioassay-guided isolation. The ethanol extract, hexane soluble fraction, dichloromethane soluble fraction and the residue were tested for their cytotoxic activity against selected cancer cell lines. Hexane soluble-fraction was selected to be further fractionated on lung cancer cell line, A549. Four sesquiterpene compounds namely spathulenol (1), β-eudesmol (2), dehydrocurdione (3) and curcumenone (4) were characterized from the active fraction H1.2. spathulenol (1), β-eudesmol (2) and dehydrocurdione (3) exhibited cytotoxic activity towards lung cancer cell lines, A549 and SK-LU-1 with IC50 values ranging from 11.0 μg/mL to 22.9 μg/mL with spathulenol being the most potent. The rhizome essential oils of C. zedoaria from Malaysia and Indonesia were obtained by hydro distillation and analysed by GC-FID, GC/MS and Kovat indices. Comparison of the main chemical constituents of both essential oils revealed camphor (17.6% and 19.7%, respectively), zerumbone (17.1% and 12.1%) and curzerenone (10.2% and 7.4%). These essential oils exhibited dose dependent cytotoxic activity (MTT assay) against cancer cell lines: breast (MCF-7 and MDA-MB-231), lung (A549 and SK-LU-1) and cervical (HeLa S3 and SiHa) with IC50 values in the range of 6.4 μg/mL to 22.0 μg/mL. Overall, Malaysian C. zedoaria essential oil showed higher potent cytotoxic activity as compared to the Indonesian essential oil towards cancer cell lines tested in particular the cervical cancer cell lines, HeLa S3 and SiHa. The IC50 values of Malaysian C. Zedoaria oil are 6.4 μg/mL for HeLa S3 and 9.8 μg/mL for SiHa while 21.6 μg/mL and 11.5 μg/mL, respectively for the Indonesian oil. The cell death of cervical cancer cell lines, HeLa S3 and SiHa was confirmed by live dead viability assay. Apoptosis was detected by Annexin V-FITC/PI assay and caspase-3/7 activity assay.